Royal Stores Ltd., MacPherson & Job Royal Stores Ltd., Water St., north side of St. John's harbour - Job, John (William John), b. 1944- (1920)
This collection consists of photographs taken from two Job family albums, reflecting their business ventures, family activities and historical events.